2001
DOI: 10.1515/cclm.2001.027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Index of Individuality on False Positives in Repeated Sampling from Healthy Individuals

Abstract: The index of individuality is defined as the ratio of the within-subject biological variation to the between-subject variation, i.e., the variation between the biological set-points. It has been disputed whether the index of individuality has influence on the usefulness of conventional population-based reference intervals. In this investigation we found that, as long as only a single sample is taken, for a certain change in an individual's set-point, the index of individuality has no influence on the usefulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 5 publications
0
34
0
Order By: Relevance
“…Sometimes the nominator also includes the analytical variation. It is suggested that if the index of individuality is between 0.6 and 1.4, then reference limits may be more useful than RCVs (23,25 ). Calculating the index of individuality in the healthy volunteers gave indices of 0.6 for both ALA and PBG.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes the nominator also includes the analytical variation. It is suggested that if the index of individuality is between 0.6 and 1.4, then reference limits may be more useful than RCVs (23,25 ). Calculating the index of individuality in the healthy volunteers gave indices of 0.6 for both ALA and PBG.…”
Section: Discussionmentioning
confidence: 99%
“…/CV G (ϭ intraindividual varianceϩanalytical variance/interindividual variance) (21,22 ). Here, a low IOI (Ͻ0.48) is considered to reflect strong individuality, which in turn indicates that an individual patient should be assessed with respect to his or her individual hormonal level.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a high IOI (Ͼ1. 4) indicates that this patient should be assessed with respect to population-derived reference intervals (21 ). Continuous data were tested by use of the 2-sample Wilcoxon test, Kruskal-Wallis-test, and 1-way ANOVA, as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…In the serial measurement situation, knowledge of the intra-individual variation is important for correct interpretation of improvement or worsening of disease (40,41). Is the difference between the previous and the current test result caused by random variation or is it a sign of change in disease activity?…”
Section: Intra-individual Variation In Thyroid Function Testsmentioning
confidence: 99%